Weighty data: importance information influences estimated weight of digital information storage devices - Schneider, Iris K.; Parzuchowski, Michal; Wojciszke, Bogdan; Schwarz, Norbert; Koole, Sander L. (Frontiers in Psychology, 2015)
Previous work has suggested that perceived importance of an object influences estimates of its weight. Specifically, important books were estimated to be heavier than non-important books. However, the experimental set-up of these studies may have suffered from a potential confound and findings may be confined to books only. Addressing this, we investigate the effect of importance on weight estimates by examining whether the importance of information stored on a data storage device (USB-stick or portable hard drive) can alter weight estimates. Results show that people thinking a USB-stick holds important tax information (vs. expired vs. no information) estimate it to be heavier (Experiment 1) compared to people who do not. Similarly, people who are told a portable hard-drive holds personally relevant information (vs. irrelevant), also estimate the drive to be heavier (Experiment 2a and 2b). The current work shows that importance influences weight perceptions beyond specific objects.